Pressão e temperatura da água de lavagem na população microbiana da superfície de carcaças bovinas - Saba, Rachel Zoccal [UNESP]; Buerger, Karina Paes [UNESP]; Rossi Junior, Oswaldo Durival [UNESP] (Universidade Federal de Santa Maria (UFSM), 2010)
The aimm of this study was to evaluate the influence of washing water temperature and pressure on mesophilic and psycluotrophic aerobic bacterial populations, yeasts and molds, total conforms and fecal coliforms population, whereas the cattle carcass surface may become contaminated during the different slaughter procedures and the final carcass washing may reduce microbial population Samples were taken by sponge swabbing in four areas of carcass surface (flank, neck, chest and rump), from which 20 were washed with write, at 25 degrees C and without artificial pressure, 20 with water under a pressure of 3atm, 20 with water at 40 degrees C and without artificial pressure and 20 with water at 40 degrees C under a pressure of 3atm For control purpose and using the same method to collect more 20 carcasses samples were taken without washing., loading 100 samples The results showed that the water at 25 degrees C undo 3atm pressure was more efficient to remove microorganisms from carcass surface than the heated water, although this latter promoter a mote visible clean carcasses
Washing water pressure and temperature on microbial population of cattle carcasses surface
Keywords: cattle carcass; cattle carcass washing; Fecal coliforms; Food safety; carcass decontamination; cattle slaughter